Reading Development and Difficulties in Monolingual and Bilingual Chinese Children
XX, 252 p. 12 illus., 8 illus. in color.
Keywords: This volume explores Chinese reading development, focusing on children in Chinese societies and bilingual Chinese-speaking children in Western societies. The book is structured around four themes: psycholinguistic study of reading, reading disability, bilingual and biliteracy development, and Chinese children’s literature. It discusses issues that are pertinent to improving language and literacy development, and complex cognitive, linguistic, and socio-cultural factors that underlie language and literacy development. In addition, the book identifies instructional practices that can enhance literacy development and academic achievement. This volume offers an integrative framework of Chinese reading, and deepens our understanding of the intricate processes that underlie Chinese children’s literacy development. It promotes research in reading Chinese and celebrates the distinguished and longstanding career of Richard C. Anderson.